Study of waveform characteristics of scintillator detector excited by ultraviolet light-emitting diodes. (25th October 2021) - Gao, T.; Yang, H.; Zhou, Y.; Yang, J.; He, Y.; Duan, H.; Feng, Y.; Yu, S.; Shen, Z.; Pan, Q.; Xiong, J.; Wang, C.; et al.
Abstract: Radioactive sources excite scintillators, causing them to emit fluorescence, and are thus widely used in studies of the performance of scintillators. Ultraviolet (UV) light-emitting diodes (LEDs) can also excite scintillators to produce fluorescence. In this paper, the waveform characteristics of a UV LED-excited scintillator detector are studied and compared with the characteristics obtained when using a radioactive source. Test results show that the trailing edge of the scintillation pulse excited by the UV LED has exponential decay characteristics that are similar to those obtained under 137 Cs excitation. The light intensity of the UV LED shows a good linear relationship with the peak position of the pulse. Furthermore, a macroscopic model for the output waveform from the scintillator when excited by a UV LED is established and the model is modified based on the experimental results. Although the scintillator's response to the UV source cannot simulate its response to gamma-ray sources fully, we hope that this method can be used in preliminary testing of scintillation detectors or when the use of radiation sources is limited.